Securing integrity of high-temperature pressure boundary components in supercritical thermal plants with application of alternative design rules. (February 2022) - Lee, Hyeong-Yeon; Eoh, Jaehyuk
Abstract: Technical issues of ASME BPVC Section VIII Division 2 (hereafter, 'ASME VIII(2)') were investigated when it was applied to design of high-temperature pressure vessels in supercritical thermal power plants subjected to long-term operation in the creep regime. The design rules of ASME VIII(2) are generally used for the design of pressure vessels operating not only at low temperature but also at high temperature in the creep range. The potential connections of ASME VIII(2) with a number of defects in pressure vessels due to technical issues on the implicit consideration of the creep effects were investigated. For the superheater component subjected to long-term operation in the creep regime, design evaluations were conducted according to ASME VIII(2) and three alternative design rules of ASME BPVC Section III Division 5 Subsection HB, French RCC-MRx and ASME Section VIII Division 2 Code Case 2843–2 that consider creep effects explicitly. Code comparisons were made in terms of conservatism. It was shown that there does exist concern about the non-conservatism of ASME VIII(2) associated with designs subjected to long-term operation in the creep range; the issues can be addressed with application of three alternative design rules to enhance integrity of pressure vessel. Highlights: Technical issues of ASME Section VIII Division 2 ('ASME VIII(2)') for pressure vessel of supercritical thermal plant in case of long-term creep exposure were investigated. Code comparisons were made in terms of conservatism among ASME VIII(2) and alternative three design rules of ASME-HB, RCC-MRx and ASME CC-2843 that consider creep explicitly. Aspects of progressive accumulation of creep damage can not be evaluated in ASME VIII(2) but can be in three alternative rules due to their explicit consideration of creep. It was shown that ASME VIII(2) can become non-conservative in case of long-term operation in the creep range because operation time does not affect the results in ASME VIII(2) design. With application of the three alternative design rules, integrity can be greatly improved for pressure vessels under long-term creep exposure in supercritical plant.